ACHILLE MBEMBE AS BLACK THEOLOGIAN. Issue 3 (July 2016) - Lloyd, Vincent
Abstract : The Cameroon-born, South Africa-based Achille Mbembe is one of the preeminent theorists of race writing today. Leading the current wave of critical race scholarship that views anti-Blackness as a metaphysical rather than merely social problem, Mbembe's work brings together the tools of psychoanalysis, critical theory, and postcolonial studies. In De la postcolonie: essai sur l'imagination politique dans l'Afrique contemparaine (2000), 1 Mbembe focuses his critical lens on Africa as object of fantasy and resistance to fantasy; in his most recent work, Critique de la raison nègre (2013), 2 Mbembe turns to the figure of the Black. While Mbembe himself offers provocative suggestions about the implications of his work for religious thought, his account of anti-Blackness as a metaphysical problem opens constructive avenues for re-thinking Black theology. When Blackness is defined by death, the critical practice Mbembe describes and commends may be understood as a form of resurrection, restoring death-bound-being to life. I argue that reading Mbembe as part of a conversation in Black theology can expand the Black theological imagination.